Effect of Solubilizers on the Androgenic Activity of Basella Alba L. (Basellaceae) in Adult Male Rats - Edouard Akono Nantia; Faustin Pascal Tsagué Manfo; Nathalie Sara E Beboy; Paul Fewou Moundipa (Tabriz University of Medical Sciences, 2017)
Purpose: Solubilizers play an important role in dissolution of pharmacological ingredients and should properly dissolve the active principle(s) while preserving its activities. This study investigated the effect of starch, gelatin, methylcellulose and polyvinylpyrrolidone 10000 in the preservation of the androgenic activity of the methanol extract Basella alba (MEBa). Methods: Different groups of male albino rats were orally given the MEBa (1 mg/kg) dissolved into either 1% gelatin (1% gel), %1 methylcellulose (1% MC) and 1% polyvinylpyrrolidone 10000 (1% PVP 10000) or 2% starch solution (2% SS) for 30 days. Thereafter, animals were sacrificed and serum testosterone and creatinine levels as well as alanine aminotransferase (ALT) activity determined. Vital and reproductive organs were dissected out and weighed, while liver thiobarbituric acid reactive substances (TBARS) and glutathione levels were determined. Results: Different treatments did not affect the animal body and organ weights. The MEBa stimulatory effect on testosterone production was preserved with 2% SS and 1% PVP 10000 as vehicles. Increased liver glutathione and TBARS levels were also observed in the animals fed with the MEBa dissolved in 2% SS and 1% Gel, respectively, while other biochemical parameters remained unchanged. Conclusion: Starch and polyvinylpyrrolidone 10000 stand as good preservation agents for MEBa androgenic activity, with starch exhibiting additional antioxidant activity through increase of glutathione levels.